Effect of dried and ensiled pomegranate by-pr oduct on performance, blood metabolites and meat quality of Balochi lambs - Hashemi Kondori, SM; Vakili, R; Ghiasi, SE (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to investigate the addition of dried and ensiled pomegranate by-products on the performance, rumen parameters, blood metabolites and meat quality of Balochi ram lambs. A total of 18 lambs at 90 d age with similar body weight (BW, 28.0±3.5 kg) with 6 replicates per treatment were used. The experimental treatments including 1) Control, 2) 20% of dried pomegranate by-product, 3) 20% of ensiled pomegranate by-product. According to the results, it was found that the use of pomegranate by-products does not have a significant effect on daily weight gain, feed consumption and feed conversion ratio (P>0.05). Except the constant rate of gas production, other rumen parameters were significantly affected by the experimental treatments (P<0.05). Furthermore, the use of pomegranate by-products had a significant effect on blood cholesterol (P<0.05). Moreover, the dietary treatments have no significant effect on meat traits and its components (P>0.05). The overall results showed that ensiling pomegranate by-products could reduce the amount of tannin in them to a greater extent.